COMBINED METHOD OF INCREASING WEAR RESISTANCE DETAILS OF TRI-BOMECHANICAL SYSTEMS - Кіндрачук, Мирослав; Духота, Олександр; Харченко, Володимир; Стебелецька, Наталія; Гловин, Андрій (Problems of Friction and Wear, 2022)
The review of modern combined technologies of nitriding and laser treatment of steel surfaces is carried out. The mechanism of damage to the steel 30Х2НВФА ball-screw lifting mechanism of the flaps of the transport aircraft, which develops due to insufficient surface hardness of the material after the conventional heat treatment, is determined. Auger spectral analysis revealed a high intensity of interaction of the material with oxygen - its concentration reaches 41.4% at. Carburization of the friction surface, especially significant on the surface of the pitting damage, the depth of which reaches 0.7 mm, was revealed. A complex technology of surface hardening of nitriding + laser discrete hardening is offered. The radiation power was 1 kW, the diameter of the focus spot was 2.5 mm and the step between the centers of the focus spots was 2.5 mm. The total area of laser treatment was 70%. The steel temperature exceeded Ас3 and corresponded to the tempering temperature range. The depth of the nitrided layer increases to 400 μm, the maximum surface hardness is 1350-1380 HV0,2. The formation of a continuous nitrided layer with a thickness of 200-250 μm and a transition zone consisting of columnar iron nitrides, which are produced in the matrix material, are observed. As a result, the sharp gradient of mechanical properties disappears. The method of fretting research in the conditions of ball contact (ball-plane) is improved. Tests have confirmed that the wear resistance of the complex treated surface is 25% higher in dry friction, and twice - in the conditions of lubrication with grease "Era" in comparison with nitrided steel according to conventional technology 30Х2НВФА. In addition, there is no brittle destruction of the surface, significantly reduces the interaction with oxygen.